2017
DOI: 10.1371/journal.pone.0187543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen levels and nitrogen ratios on lodging resistance and yield potential of winter wheat (Triticum aestivum L.)

Abstract: Lodging is one of the constraints that limit wheat yields and quality due to the unexpected bending or breaking stems on wheat (Triticum aestivum L.) production worldwide. In addition to choosing lodging resistance varieties, husbandry practices also have a significant effect on lodging. Nitrogen management is one of the most common and efficient methods. A field experiment with Yangmai 20 as research material (a widely-used variety) was conducted to study the effects of different nitrogen levels and ratios on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
67
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 33 publications
16
67
0
4
Order By: Relevance
“…The stem strength also indicated positive correlations with chain weight, LRFI, grain yield, grain weight and harvest index. The results obtained are in conformity with Zhang et al, 2017. The second-internodal length of dwarf genotypes was significantly lower than the tall genotypes at all the growth stages.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The stem strength also indicated positive correlations with chain weight, LRFI, grain yield, grain weight and harvest index. The results obtained are in conformity with Zhang et al, 2017. The second-internodal length of dwarf genotypes was significantly lower than the tall genotypes at all the growth stages.…”
Section: Resultssupporting
confidence: 88%
“…Plant height has been the main target for the improvement of lodging resistance. Plant breeders have reduced lodging risk by introducing dwarfing genes to decrease plant height which is negatively correlating with lodging resistance, but the reduction in plant height to improve lodging resistance could reduce the photosynthetic capacity resulting reduction of yield (Zhang et al, 2017). What has not been achieved is good lodging resistance in all short spring wheats, nor a complete understanding of its physiological basis.…”
Section: Al 2000)mentioning
confidence: 99%
“…Arduini et al, (2006) reported the application of N improves the grain size and grain N content. Zhang et al,(2017)the observed in uence of N fertilizer was highly signi cant on grain yield and TGW.…”
Section: Thousand Grain Weight (G)mentioning
confidence: 95%
“…Відомо [1,2], що саме показники фотосинтетичної діяльності часто корелюють із зерновою продуктивністю рослин. На рівень накопичення фотосинтетичних пігментів впливає також живлення посівів, у тому числі й добривами у разі їх позакореневого застосування [2,9,22,28]. Однак дані щодо фізіологічної взаємодії сучасних ретардантів у композиціях із добривами за позакореневого застосування обмежені.…”
unclassified